CONVERSATION ANALYSIS ON THE INTERVIEW TEST OF THE INDONESIAN SOLIDARITY PARTY’S LEGISLATIVE CANDIDATES - Wijayanti, Farida Indri (Masyarakat Linguistik Indonesia, 2020)
Based on an analysis of 154 questions and their responses in the interview test of the Indonesian Solidarity Party’s legislative candidates, this article gives a descriptive overview of interview stages and the types of question-response that are implemented in the conversation. Conversation Analysis (CA) is applied as an approach. Data are from video recordings of naturally occurring conversation in the interview test that are retrieved from https://www.youtube.com. Relying on the data, this paper shows the generic structure of interview test (e.g., warm-up, confirmation, information exchange, and wrap-up), question types (e.g., wh-, disjunctive, declarative, tag, echo, narrative, and multiple), and types of responses (e.g., information, confirmation, marked confirmation, disconfirmation, choice of alternative answers, implication, code switched, and repetition). This paper reveals that wh-interrogative is used more commonly in the interview test than the other question types. Finally, information response in the form of clausal responses is mostly preferred by legislative candidates.